Essential Oils of Plants as Biocides against Microorganisms Isolated from Cuban and Argentine Documentary Heritage - Borrego, Sofía (2012)
Natural products obtained from plants with biocidal activity represent an alternative and useful source in the control of biodeterioration of documentary heritage, without negative environmental and human impacts. In this work, we studied the antimicrobial activity of seven essential oils against microorganisms associated with the biodeterioration of documentary heritage. The essential oils were obtained by steam distillation. The antimicrobial activity was analyzed using the agar diffusion method against 4 strains of fungi and 6 bacterial strains isolated fromrepositories air and documents of theNational Archive of the Republic of Cuba and theHistorical Archive of theMuseum of La Plata, Argentina. Anise and garlic oils showed the best antifungal activity at all concentrations studied, while oregano oil not only was effective against fungi tested but also prevented sporulation of them all. Orange sweet and laurel oils were ineffective against fungi. Clove, garlic, and oregano oils showed the highest antibacterial activity at 25% against Enterobacter agglomerans and Streptomyces sp., while only clove and oregano oils were effective against Bacillus sp. at all concentrations studied. This study has an important implication for the possible use of the natural products from plants in the control of biodeterioration of documentary heritage.